Saṅkalpa : ('Oḍiyā sāhitya samāja' ra mukhapatra) : sāhitya samāḷocanā biśēṣaṅka (Oriyā Bhāṣā o Sāhitẏa Bibhāga, Jātīyakabi Bīrakiśōra Sarakārī Mahābidẏālaya, 2010)
Contributed articles on Oriya literature